The impact of the cooperative learning strategy in improving the performance of eighth grade students in reading comprehension and motivation of learning - Alazzam, Anwar Abdulkarim Mattar (Journal of Educational and Psychological Sciences, 2020)
The study aimed at revealing the impact of the cooperative learning strategy in improving the performance of eighth grade students in reading comprehension and motivation of learning. The study was limited to the eighth grade students in the schools of Irbid governorate. In the second semester of the academic year 2018/2019 was followed the approach semi-experimental, In order to achieve the objective of the current study، Where the members of the sample of students from the eighth grade to two tests on the tool to measure the strategy of cooperative learning، one of them the prior and the other post, This type is depends on one group and considered as a case study, and by presence of prior measurement that provides some information on the performance of the study group before the experiment to be then - compared prior -measurement by post-measurement The study reached the following results: - There were statistically significant differences at the level of statistical significance (α≤0.05) In the average signs of students in the experimental group (who are studying using a cooperative learning strategy) and the average signs of students in the control group (who are studying using the normal method) in the test to solve the post-reading comprehension. - There were statistically significant differences at the level of statistical significance (α≤0.05) average student signs in the experimental group (Who are studying using a cooperative learning strategy) and average student signs in the control group (who study using the usual method) In the test of solving the comprehension of post-reading, when reviewing the arithmetic averages, the differences were found to be in favor of the experimental group; It reached the arithmetic average of the experimental group (17.43) while the arithmetic average of the control group (13.34) which indicates the high skill of solving reading comprehension among members of the experimental group compared to the control group, This indicates a positive impact of the use of collaborative learning in improving students’ ability to solve reading comprehension In the light of the findings of the study, the researcher made several recommendations, including: Modern teaching strategies use modern teaching in the teaching of Arabic language because of their positive impact on positive learning. The need for the teachers of Arabic to know the modern teaching strategies to learn and teach different language skills.